The effect of incorporation of prepared Ag-Zn Zeolite on some properties of heat polymerized acrylic denture base materials - Zainab A Azeez; Nabeel A Fatah (College of Dentistry/ University of Baghdad, 2015)
Background: Poly (methylmethacrylate) is the most widely used material in denture fabrication. The characteristics of acrylic resin which support microorganism development can threaten the oral health of denture users. This study was assigned to prepareand incorporate Ag-Zn zeolite powder into heat cured denture base material as antimicrobial material and to investigate its effect on some properties of heat cured acrylic denture base materials. Materials and methods: Sliver -zinc zeolite was prepared by ion exchange method and characterized then incorporated into poly (methylmethacrylate) powder in0.5% by weight. Specimens were constructed and divided into 6 groups according to the using tests; each group was subdivided into 2 groups. The tests conducted in this study were: impact strength test, transverse strength test, surface hardness test, surface roughness test, water sorption test, water solubility test and color change measurement after addition. The results were statistically analyzed by t-test at p value≤ 0.05. Results: Characterization methods results showed the incorporation of sliver and zinc ion without change of zeolite structure framework. A non-significant effect resulted from the addition of 0.5% sliver -zinc zeolite on the impact strength, transverse strength, surface hardness, surface roughness and cause no change in color of heat cure denture base. Also a highly significant decrease in water sorption and a significant increase of water solubility were observed. Conclusion: Preparation of sliver-zinc zeolite could be performed successfully and the addition of 0.5% of antimicrobial sliver-zinc zeolite into heat cure acrylic had a non significant effect on the impact strength, transverse strength, surface hardness, surface roughness and did not change the color, also there was a significant decrease in water sorption and increase in water solubility of acrylic resin. Key words: Denture stomatitis, Antimicrobial agent, Ag- Zn Zeolite.